UNUSUAL LOCALIZATION OF A COMAMONAS KERSTERSII : A CASE REPORT - Andriamampionona, Ginnot; Yves T, Rabetokotany; Andotiana D, Rabarijaona; Nandrianina R, Mananjara; Andriarimanana HN, Rakotoarisoa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Comamonas kerstersii is a gram-negative, opportunistic and phytopathogenic bacterium. Usually in humans, this germs is responsible for intra-abdominal infections and some genital infections. It is also found in water, soil and especially plants. However, the otological location of this microorganism is unusual. We report a case of a 29-year-old housewife, with no particular history, coming in consultation for chronic right unilateral otorrhea. The patient had received empirical treatment with a purulent otitis, but no satisfactory improvement. This situation leads us to perform a cytobacteriological examination by swabbing auricular flow. This assessment had found a kerstersii comamonas resistant to our first line anti-infective treatment. This causal germ was only susceptible to amikacin depending on the outcome of the antibiogram. Healing was notable after 5 days of local and general treatment adapted